A retrospective study of azithromycin and ceftizoxime for the management of children with Mycoplasma pneumoniae pneumonia. Issue 44 (5th November 2021) - Han, Li-ping; Xiao, Han-yan; Fang, Li-li
Abstract : Abstract: The aim of this study was to compare the clinical efficacy of azithromycin and ceftizoxime (AC) and erythromycin and amoxicillin/sulbactam (EAS) in the treatment of children with Mycoplasma pneumoniae pneumonia (MPP). In this retrospective study, a total of 92 eligible children with MPP were included, and they were divided into a treatment group (n = 46) and a control group (n = 46). All patients were treated with intravenous ambroxol, and nebulized inhalation of budesonide and terbutaline. In addition, patients in the treatment group received AC. Patients in the control group underwent EAS. All patients in both groups were treated for a total of 10 days. Outcomes consist of erythrocyte sedimentation rate, C-reactive protein, serum lactate dehydrogenase, and interleukin 6, fever clearance time, time of cough disappearance, time of rale disappearance, time of signs disappeared by X-ray, and adverse events. All outcomes were measured after 10-day treatment. After treatment, patients who received AC exerted better improvements in erythrocyte sedimentation rate ( P  < .01), C-reactive protein ( P  < .01), serum lactate dehydrogenase ( P  < .01), interleukin 6 ( P  < .01), fever clearance time ( P  < .01), time of cough disappearance ( P  < .01), time of rale disappearance ( P  < .01), and time of signs disappeared by X-ray ( P  < .01), than those in patients who received EAS. In addition, there were not significant differences in adverse events between 2 groups. The results of this study showed that AC may benefit more than EAS for the children with MPP.